2020
DOI: 10.1371/journal.pone.0228451
|View full text |Cite
|
Sign up to set email alerts
|

Viral reactivations following hematopoietic stem cell transplantation in pediatric patients – A single center 11-year analysis

Abstract: Viral reactivation occurs frequently in the context of immunodeficiency and immunosuppression after allogeneic hematopoietic stem cell transplantation (allo-HSCT) and can cause severe complications. The aim of this single-center retrospective analysis was to characterize viral infections in the first year after HSCT, to investigate risk factors and to study the impact of viral infections on transplantation outcome. This will facilitate the identification of at-risk patients and the development of new preventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 52 publications
4
45
2
2
Order By: Relevance
“…In two studies, aGvHD was dichotomized in grade ≥3 versus <3; one of them (Juvonen et al [ 66 ]) showed that patients with aGvHD grade ≥3 had a higher risk of active EBV infection (HR = 1.70 (95% CI: 1.11–2.62)). However, this result was not corroborated by other studies [ 51 , 91 , 101 ]. Among eight studies [ 4 , 39 , 41 , 57 , 59 , 74 , 86 , 89 ] that compared grade ≥2 versus <2, two [ 59 , 89 ] showed that an aGvHD grade ≥2 significantly increased the risk of active EBV infection, one reported a positive association without reporting the relative risk (Hiwarkar et al [ 58 ]), and the other (Sirvent-Von Bueltzingsloewen et al [ 89 ]) reported an OR = 3.4 (95% CI: 1.2–9.7).…”
Section: Resultscontrasting
confidence: 98%
See 2 more Smart Citations
“…In two studies, aGvHD was dichotomized in grade ≥3 versus <3; one of them (Juvonen et al [ 66 ]) showed that patients with aGvHD grade ≥3 had a higher risk of active EBV infection (HR = 1.70 (95% CI: 1.11–2.62)). However, this result was not corroborated by other studies [ 51 , 91 , 101 ]. Among eight studies [ 4 , 39 , 41 , 57 , 59 , 74 , 86 , 89 ] that compared grade ≥2 versus <2, two [ 59 , 89 ] showed that an aGvHD grade ≥2 significantly increased the risk of active EBV infection, one reported a positive association without reporting the relative risk (Hiwarkar et al [ 58 ]), and the other (Sirvent-Von Bueltzingsloewen et al [ 89 ]) reported an OR = 3.4 (95% CI: 1.2–9.7).…”
Section: Resultscontrasting
confidence: 98%
“…In total, 3362 titles were identified in the research bases, 1883 in EMBASE and 1479 in Medline. Once duplicates and papers with exclusion criteria were removed, 77 articles [ 4 , 16 , 23 , 24 , 27 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytomegalovirus, Epstein–Barr virus, and adenovirus constitute the majority of significant viremias after HCT. Transplant-related variables that contribute to the risk include the underlying disease, donor and graft source, preparative regimen, and the degree of T cell depletion ( in vivo or ex vivo ) ( 85 , 86 ). Current pharmacologic antiviral prophylaxis and treatment are limited in efficacy and are toxic to various organs ( 87 , 88 ).…”
Section: Strategies For Early Hematopoietic Recoverymentioning
confidence: 99%
“…A szekunder immundefi ciencia és az immunszuppreszszió miatt a beavatkozás egyik leggyakoribb szövődménye a vírusreaktiváció [5]. Az akut graft -versus-host betegség (GVHD) gyakoriságát és súlyosságát többek közt a transzplantáció és a graft típusa befolyásolja [6].…”
Section: Bevezetésunclassified